Proper Immune Response Depends on Early Exposure to Gut Microbiota in Broiler Chicks - Rodrigues, Denise R.; Wilson, Kim M.; Bielke, Lisa R. (Frontiers in Physiology, 2021)
The successional changes in the early intestinal microbiota occur concomitantly with the development, expansion, and education of the mucosal immune system. Although great attention of researchers has been focused on understanding the linkage between microbiota and immune functions, many essential details of the symbiotic relationship between the intestinal pioneer microbiota and the avian immune system remain to be discovered. This study was conducted to understand the impact of different early life intestinal colonizers on innate and adaptive immune processes in chicks, and further identify immune-associated proteins expressed in the intestine tissue. To accomplish it, we performed an in ovo application of two apathogenic Enterobacteriaceae isolates and lactic acid bacteria (L) to determine their influences on the intestinal proteome profile of broilers at day of hatch (DOH) and 10 days of old. The results indicated that there were predicted biological functions of L-treated chicks associated with activation and balanced function of the innate and adaptive immune systems. At the same time, the Enterobacteriaceae exposed birds presented dysregulated immunological mechanisms or a downregulated processes related to immune development. Those findings suggested that a proper immune function was dependent on specific gut microbiota exposure, in which the prenatal probiotic application may have favored the fitting programming of immune functions in chicks.